2009
DOI: 10.1152/ajpregu.00174.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characterization and hemodynamic effects of pulmonary waves in fetal lambs using cardiac extrasystoles and beat-by-beat wave intensity analysis

Abstract: Smolich JJ, Mynard JP, Penny DJ. Dynamic characterization and hemodynamic effects of pulmonary waves in fetal lambs using cardiac extrasystoles and beat-by-beat wave intensity analysis. Am J Physiol Regul Integr Comp Physiol 297: R428 -R436, 2009. First published June 3, 2009 doi:10.1152/ajpregu.00174.2009.-Steadystate wave intensity (WI) analysis indicates that characteristic midsystolic falls in fetal pulmonary trunk (PT) and artery (PA) blood flow are due to an extremely large backward-running compression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(52 citation statements)
references
References 49 publications
3
49
0
Order By: Relevance
“…a beat with a long diastole) was initiated with a brisk tap to the right ventricular infundibulum using forceps [41]; this beat was then used for analysis. Signals were filtered using a 48 Hz low-pass filter and flow was converted to velocity using the nominal size of the flow probe [7,11,12,41,42]. Wave speed (c) was calculated using the pu-loop method [28,43,44].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…a beat with a long diastole) was initiated with a brisk tap to the right ventricular infundibulum using forceps [41]; this beat was then used for analysis. Signals were filtered using a 48 Hz low-pass filter and flow was converted to velocity using the nominal size of the flow probe [7,11,12,41,42]. Wave speed (c) was calculated using the pu-loop method [28,43,44].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Despite the close anatomical proximity, however, the blood flow profile of the DA is strikingly different from that of the PT or PA. Thus, both the PT and PA demonstrate a flow peak in early systole but, particularly in the main and large branch PA, flow then falls abruptly in midsystole, even though pulmonary blood pressure continues to rise (19,29,36,37). By contrast, DA flow also rises in early systole but then increases further in midsystole to a delayed peak (31).…”
mentioning
confidence: 99%
“…This approach is founded on the premise that cardiovascular function is accompanied by the propagation of infinitesimal wave fronts defined by their pressure (P) and velocity (U) effects (2,23), with the product of changes in P and U in the time domain (i.e., "WI") related to the instantaneous energy carried by the wave fronts. Using WI analysis (36,37), we recently demonstrated that the midsystolic fall in fetal PA blood flow was caused by an unusually large PA backward-running compression wave (BCW ms ) that originated in the pulmonary microvasculature and was of similar or greater magnitude than the forward-running compression wave (FCW is ) associated with impulsive RV ejection of blood. Furthermore, retrograde transmission of ϳ25% of PA BCW ms energy into the PT (36) produced the midsystolic fall evident in the flow/velocity profile of this vessel (10,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…WIa performed in the beats surrounding an ectopic beat, showed that there is a close relationship between the BCWpulm_foet_pa and the preceding FCWpulm on a beat-to-beat basis, with matching transient potentiation in both waves after an ectopic beat. This relationship highlighted the possible role of the BCWpulm_foet_pa in the regulation of pa and pT hemodynamics 66 . This wave is also transmitted into the Da as a FCW (FCWpulm_foet_Da) and is responsible for augmentation in Da mid-systolic blood flow, a mechanism that supports foetal right-to-left flow at a period in the cardiac cycle where pT and pa flows are decreasing 67 .…”
Section: Pulmonary Wave Intensity In the Foetal Circulationmentioning
confidence: 85%